SAT0688 PATIENT STATE OF KNOWLEDGE ON BIOSIMILARS – DO PHYSICIANS NEED TO IMPROVE EDUCATION SKILLS?. (June 2019) - CLAUDIA, COBILINSCHI; Opris-Belinski, Daniela; Codreanu, Catalin; Ionescu, Razvan; Mihailov, Claudia; Parvu, Magda; Popoviciu, Horatiu; Rezus, Elena; Ionescu, Ruxandra
Abstract : Background: Biosimilars are highly similar to original biological medicines 1 .Worldwide prescription of biosimilars is still low because of the lack of understanding in manufacturing and approval process together with mistrust in the extrapolation of indication in clinical use 2 .Lack of biosimilar awareness throughout rheumatic patients results in an unjustified underuse 2 . Objectives: To assess patients' current knowledge and concerns on biosimilars and to investigate their expectations when receiving such a treatment following the principle of shared-decision making. Methods: A national, cross-sectional survey was conducted in Romanian patients with rheumatoid arthritis(RA), spondyloarthritis(SpA), psoriatic arthritis(PsA)currently on a bio-originator or biosimilar.336 patients responded to a survey distributed from August to December 2018, main topics being patient basic information on biosimilars, their efficacy, safety, price or differences to original drugs. Results: Out of 336 patients, 47.3% had RA, 39.8% SpA, 12.5% PsA with a mean age of 52.5.In the study cohort, 13% received approved biosimilars while 87% bio-originators with different mechanisms of action.A yes/no type of question divided patients into those aware or not of biosimilars with further exclusion of those with lack of information.Half of the patients(48.8%) stated they never heard of biosimilars.Surprisingly, four of them were already on this type of treatment.Out of the 172 remaining patients, 28.4% feared the risk of adverse events like infections or cancer while almost 20% expressed either insecurity on drug tolerability or the possibility that the biosimilar might be less efficient that the original drug.Another 19.7% certified they had no concerns related to these products and only 15.1% stated confusion regarding the potentially difference in the pharmacological structure of the drugs.Most patients(48.2%) are convinced that the price of a drug should not exceed its efficacy or safety.Half of the respondents say they could accept a switch from an original to a biosimilar if their rheumatologist advises them and 30% might agree but only after being informed.8.7% are interested in scientific proof of the drug and only 1% would consent to a change directly from the pharmacist.When handling prescription, 37.7% of patients would want to know if it is an original drug or a biosimilar while 20% do not mind if they receive either.Another 30% trust their rheumatologist and 12.7% would feel more secure if receiving a patient card and written information.Most patients(73.2%)say that they feel completely confident in their rheumatologist if they would want to prescribe a biosimilar, 18.6% will have doubts but they will accept the drug and 4% would ask for another medical opinion.After biosimilar initiation, 45.9% would be cautious when administrating it, 23.2% would stop the drug if an adverse event occured and 15% would have no fears. Conclusion: Study results confirm there is still a significant information gap concerning biosimilars in patient population.Most concerns on biosimilars are related to adverse event occurrence.There is a need to improve patient education on biosimilars involving patients and health professionals.Shared-decision principle is more of a myth since most patients rely entirely on their physician for prescribing the most appropriate product. Reference: [1] Declerck P, et al. The Language of Biosimilars:Clarification, Definitions and Regulatory Aspects.Drugs 2017. 2.O'Callaghan J, et al. Regulatory Science Ireland:bridging the information gap on biosimilar medicines.GaBI J 2016. Disclosure of Interests: CLAUDIA COBILINSCHI: None declared, Daniela Opris-Belinski Grant/research support from: GLORIA, Speakers bureau: multiple, Catalin Codreanu: None declared, Razvan Ionescu Speakers bureau: multiple, Claudia Mihailov Speakers bureau: Abbvie, Pfizer, Novartis, MSD, Roche, Biogen, UCB, Lilly, Magda Parvu: None declared, Horatiu Popoviciu: None declared, Elena Rezus: None declared, Ruxandra Ionescu: None declared